Natural gas‐fueled multigeneration for reducing environmental effects of brine and increasing product diversity: Thermodynamic and economic analyses. Issue 3 (16th December 2022) - Ehyaei, M. A.; Kasaeian, M.; Abanades, Stéphane; Razmjoo, Armin; Afshari, Hamed; Rosen, Marc A.; Das, Biplab
Abstract: Water scarcity threatens human life and it is likely to be a main concern in the next century. In this work, a novel multigeneration system (MGS) is introduced and assessed with energy, exergy, and economic analyses. This MGS includes a gas cycle, multieffect distillation, an absorption refrigeration cycle, a heat recovery steam generator, and electrodialysis. Electrodialysis is integrated into this configuration to produce sodium hydroxide and hydrogen chloride from brine to prevent its release to the environment with harmful impacts. The other products are electricity, cooling, and demineralized water. For the evaluation of the proposed system, one computer code is provided in engineering equation solver software. For physical properties calculation, the library of this software is used. The MGS produces 614.7 GWh of electrical energy, 87.44 GWh of cooling, 12.47 million m 3 of demineralized water, and 0.092 and 0.084 billion kg of sodium hydroxide and hydrogen chloride over a year. Energy and exergy evaluations demonstrate that the MGS energy and exergy efficiencies are 31.3% and 18.7%, respectively. The highest and lowest value of exergy destruction rate is associated with the combustion chamber and pump, respectively. The economic evaluation indicates that the net present value of this proposed system is 3.8 billion US$, while the internal rate of return and payback period, respectively, are 0.49 and 2.1 years. Abstract : This multigeneration system includes a gas cycle, multieffect distillation, an absorption refrigeration cycle, a heat recovery steam generator, and electrodialysis. Electrodialysis is integrated into this configuration to produce sodium hydroxide and hydrogen chloride from brine to prevent its release to the environment with harmful impacts. The other products are electricity, cooling, and demineralized water.